Behind closed doors: the DC-10 and the demise of McDonnell Douglas. Issue 6 (30th March 2019) - Licht, John-Gabriel; O'Brien, Jamie; Schaffer, Marc
Abstract : Theoretical basis: This case has three primary objectives. First, it allows students to think through a conceptual cost and benefit analysis associated with the decision-making process in line with basic economic thinking. Students will revisit core concepts of marginal benefit vs marginal cost, the notion of opportunity costs and the role of sunk costs in this type of analysis, while also highlighting the nature of market structure, oligopolies and competition across firms in an industry. The second goal of this case is to consider the role of business ethics in the DC-10 case: specifically, to consider the potential influence of moral awareness and moral disengagement in unethical decisions made by McDonnell Douglas. Students will develop an understanding of these concepts and solidify their learning by applying them to the case and engaging in active discussion. Finally, the third goal of the case allows students to explore organizational culture and specifically offer recommendations for organizations thinking about the link between decision-making, the role of ethics and culture. Research methodology: The technical reports released by the National Transportation Safety Board along with secondary data such as available public data such as news reports were used to round out the synopsis of the case study. Case overview /synopsis: This case explores the accidents of two McDonnell Douglas DC-10s in the early 1970s at the onset of the jumbo jet race between Boeing, Lockheed and McDonnell Douglas. It explores the series of events during the "Windsor Incident" in 1972 and the subsequent accident over Paris in 1974. It explores the reasons why the cargo door on the DC-10 was faulty and subsequently why the door was not fixed. It examines the interplay of industry suppliers such as McDonnell Douglas and how they interact with oversight authorities such as the Federal Aviation Authority. The Teaching Note focuses on the economic thinking at McDonnell Douglas, behavioral ethics and organizational culture. Complexity academic level: This case is best explored over a 90 min session but could be expanded to take up one 3 h session. The authors have used this case format in an undergraduate organizational behavior class, an MBA Leadership and Organizational Change class, and an MBA Economics of Managers class. It works particularly well in the MBA setting, as students with work experience can see the links between the mistakes made by McDonnell Douglas and their workplaces.